Processus dynamiques de reconstitution dans la série du Quercus ilex en Corse - Allier, C; Lacoste, A (Plant Ecology, 1981)
The use of permanent plots in representative sites of various phytosociologically defined stages of the Quercus ilex series in N W Corsica allows us to analyse the natural dynamical process occurring in the development sequence. The regular floristic analysis of stands and transects (mainly using a linear cover measure) during 5 yr not only shows variations of composition and structure but also results in a diachronic understanding of the temporal relations between the stages. The study of forest plots (structure, n u m b e r and development of seedlings) enables us to generalize the principle of ponctual and cyclic self-transformation of climatic and subclimatic stages.
Keywords: Diachronic study; Permanent plots; Quercus ilex series; Transects